The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1116/1.2815690
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials and nanoparticles: Sources and toxicity

Abstract: This review is presented as a common foundation for scientists interested in nanoparticles, their origin, activity, and biological toxicity. It is written with the goal of rationalizing and informing public health concerns related to this sometimes-strange new science of 'nano', while raising awareness of nanomaterials' toxicity among scientists and manufacturers handling them. We show that humans have always been exposed to tiny particles via dust storms, volcanic ash, and other natural processes, and that ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
1,669
1
67

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,060 publications
(1,866 citation statements)
references
References 311 publications
10
1,669
1
67
Order By: Relevance
“…If NPs form clusters, they may behave like larger particles due to their increased hydrodynamic size (Buzea, Pacheco, & Robbie, 2007). Since agglomeration could affect critical physico-chemical features such as particle size and size distribution, the biological effects of these changes should be identified to avoid incorrect estimation of toxic potential of ENMs (Dhawan & Sharma, 2010;Jiang, Oberdörster, & Biswas, 2009).…”
Section: Aggregation Statementioning
confidence: 99%
“…If NPs form clusters, they may behave like larger particles due to their increased hydrodynamic size (Buzea, Pacheco, & Robbie, 2007). Since agglomeration could affect critical physico-chemical features such as particle size and size distribution, the biological effects of these changes should be identified to avoid incorrect estimation of toxic potential of ENMs (Dhawan & Sharma, 2010;Jiang, Oberdörster, & Biswas, 2009).…”
Section: Aggregation Statementioning
confidence: 99%
“…Quando o termo C nm ({R}, ∇) é nulo, é possível escrever a equação de Schrödinger à luz da abordagem de Born-Oppenheimer para cada movimento nuclear, isto é, 9) em que E ele,m ({R}) é o potencial efetivo para o movimento nuclear para um conjunto de pontos fixos em {R}, definindo uma superfície de energia potencial (SEP). Por sua vez, quando C nm ({R}, ∇) é não-nulo, diz-se que o sistema é não-adiabático, pois diferentes estados encontram-se acoplados.…”
Section: Conclusãounclassified
“…Os efeitos quânticos ocorrem devido à discretização dos estados eletrônicos devido ao confinamento dos elétrons no espaço. 8,9 Nesse texto, o termo nanocluster unário é usado para se referir a partículas compostas por um único metal e o termo nanoliga é usado para se referir a partículas compostas por dois ou mais metais. Os nanoclusters metálicos são altamente sensíveis à variação de tamanho e geometria, podendo apresentar propriedades físico-químicas diferenciadas pelo acréscimo ou decréscimo de um único átomo na estrutura.…”
Section: Introductionunclassified
“…1 However, many researches indicated that, not all uses of nanomaterials in food and agriculture will result in exposure, and not all exposure will result in risk. 6 Nowadays, many…”
Section: Editorialmentioning
confidence: 99%